Organophosphorus pesticide mixture removal from environmental matrices by a soil Streptomyces mixed culture - Briceño, Gabriela (2017)
The current study aimed to evaluate the removal of a pesticide mixture composed of the insecticides chlorpyrifos (CP) and diazinon (DZ) from liquid medium, soil and a biobed biomixture by a Streptomyces mixed culture. Liquid medium contaminated with 100 mg L−1 CP plus DZ was inoculated with the Streptomyces mixed culture. Results indicated that microorganisms increased their biomass and that the inoculum was viable. The inoculum was able to remove the pesticide mixture with a removal rate of 0.036 and 0.015 h−1 and a half-life of 19 and 46 h−1 for CP and DZ, respectively. The sterilized soil and biobed biomixture inoculated with the mixed culture showed that Streptomyces was able to colonize the substrates, exhibiting an increase in population determined by quantitative polymerase chain reaction (q-PCR), enzymatic activity dehydrogenase (DHA) and acid phosphatase (APP). In both the soil and biomixture, limited CP removal was observed (6–14%), while DZ exhibited a removal rate of 0.024 and 0.060 day−1 and a half-life of 29 and 11 days, respectively. Removal of the organophosphorus pesticide (OP) mixture composed of CP and DZ from different environmental matrices by Streptomyces spp. is reported here for the first time. The decontamination strategy using a Streptomyces mixed culture could represent a promising alternative to eliminate CP and DZ residues from liquids as well as to eliminate DZ from soil and biobed biomixtures.